Philosophy and poetry:: a dialogue - Candido, Gisele Batista (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
Considering the history of Philosophy, we can see that, before recognizing and stating the peculiarities of its practices, the philosophical discourse was born in intimate connection to poetry. By exploring moments of tension and proximity between poetic and philosophical discourses, the present essay is a reflection on this relationship over time. In order to do so, we focus on the works of authors such as Homer, Plato, Goethe, F. Schlegel, and Schelling as a strategy to show variations and emphasize some specific movements within this long dialogue.